Cybercrime as a New Object of Statistical Analysis - A. E. Lyapin (Статистика и экономика, 2021)
A global trend in recent years is the so-called digitalization of crime, that is, the use of information technology as a means and instrument of crime. Remote methods of committing crimes have become widespread, in which direct contact is excluded not only between the offender and the victim, but also between the accomplices of illegal activities. The real damage from cybercrimes is currently difficult to calculate, while the number of these crimes is growing rapidly from year to year. This study analyzes the state and dynamics of crimes in the field of information technology, as well as identifies gaps in legislation, law enforcement practice and accounting in which information about crimes of this type is accumulated. Purpose of the research. The purpose of the research is to conduct a comprehensive analysis of the state and dynamics of crimes in the field of information technology. Within the framework of the article, it is necessary to give a definition of crimes in the field of information technology for the purpose of conducting static analysis, while distinguishing between identical concepts. Highlight the main types and methods of their commission, form the classification of crimes in the field of information technology and designate the criteria for their construction. Analyze the experience of foreign countries and the results of the operational activities of the economic security and anti-corruption units of the territorial internal affairs bodies and suggest measures to improve the efficiency of the work being done.Materials and methods. When writing the work, the author used the methods of mathematical statistics; methods of the general theory of statistics, namely, relative, absolute and average values, methods of synthesis and analysis. For visual display of statistical data, graphical and tabular methods of data visualization were used. The information and empirical base was compiled by data on crimes in this area of the Main Information and Analytical Center of the Ministry of Internal Affairs of Russia, the Judicial Department under the Supreme Court and the General Prosecutor’s Office of the Russian Federation.Results of the research. When writing the article, a quantitative assessment of the state of crime in the field of information technology was made, the main objects of attack by cybercriminals were identified; the most characteristic features and methods of committing crimes in the field of information technology were described. A statistical classification system for assessing the level of cybercrime is proposed. The effectiveness of the work carried out by law enforcement agencies to counter these criminal manifestations has been analyzed. Various ways of increasing the efficiency of the work of law enforcement agencies are proposed. When analyzing the law enforcement practice, a number of problems were identified related to the proof of crimes of this orientation, namely, insufficient interaction between law enforcement agencies, on the one hand, and financial institutions, telecommunication service providers, on the other hand.Conclusion. The author proposes ways to improve the quality of the verification measures to identify persons involved in the commission of crimes in the field of information technology, as well as to assess the effectiveness of economic security and anti-corruption units of territorial internal affairs bodies in identifying this category of crimes. These measures are not exhaustive; in order to increase the effectiveness of countering cybercriminals, it is necessary to apply a systematic approach aimed not only at improving the quality of the work of law enforcement and investigative agencies, improving the software system and material and technical equipment, but also improving information support of the banking sector, increasing bank response measures, and most importantly, the literacy of the population.